PENEGAKAN HUKUM PEMILU LEGISLATIF 2019 PADA DAERAH PEMILIHAN (DAPIL) SURABAYA-4: PENEGAKAN HUKUM PEMILU LEGISLATIF 2019 PADA DAERAH PEMILIHAN (DAPIL) SURABAYA-4 - Eswati (Lex Journal: Kajian Hukum & Keadilan, 2021)
That there was a shift in the results of the vote acquisition of political party candidates in the Suarabay-4 Electoral District due to an error in recording the vote acquisition from DAA-1 Plano to DAA-1 which was printed for the votes acquired by TPS 30 and TPS 31, Putat Jaya Sub-district, Sawahan District, and TPS 50 Sub-district. Simomulyo Baru, Sukomanunggal Sub-district, revealed the fact that the Surabaya City Bawaslu Decision Number 53/LP/PL/KOTA/16.01/V/2019, which stated that PPK Sawahan and PPS Kelurahan Putat Jaya were proven to have violated the procedures and procedures for the recapitulation of votes. In the trial the Constitutional Court canceled the General Election Commission Decision Number 987/PL.01.8-Kpt/06/KPU/V/2019 concerning Determination of the Results of the General Election of the President and Vice President, Members of the People's Representative Council, Regional Representatives Council, Provincial Regional People's Representative Council and the National Regency/City Regional People's Representative Council in the 2019 General Election, dated May 21, 2019, as long as it concerns the vote acquisition for Candidates for Members of the Surabaya City Regional People's Representative Council, Surabaya-4 Electoral District; Ordered the General Election Commission in casu, the General Elections Commission of Surabaya City to recount ballots at TPS 30 and TPS 31, Putat Jaya Sub-district, Sawahan District, and TPS 50 Simomulyo Baru Sub-District, Sukomanunggal Sub-district, Surabaya City on the Golkar Party's vote acquisition for this type of vote. election of candidates for members of the Surabaya City DPRD for the Surabaya electoral district 4